Jenis Flora Asing Invasif di Taman Nasional Gunung Gede Pangrango, Jawa Barat - Uji, Tahan; Sunaryo,, Sunaryo; Rachman, Erlin; Tihurua, Eka Fatmawati (Universitas Atma Jaya Yogyakarta, 2010)
Ecological study of Invasive Alien Species (IAS) at two altitudes in Mount Gede PangrangoNational Park was carried out by using quadrate method. The studied plots located at altitude1400 m and 1500 m a.s.l, in 0.2 ha each. The result shows that 45 species of trees, 77 species ofsaplings and 48 species of seedlings were recorded. Five species (i.e. Bartlettina sordida,Austroeupatorium inulaefolium, Cestrum aurantiacum, Brugmansia suaveolens and Passiflorasuberosa) are catagorized as IAS which threaten the ecosystem and natural species.